Simulation-Based System Modeling of Grazing Land Management for Beef Cattle Development in East Luwu, Indonesia - Sema Sema; Jasmal Ahmari Syamsu; Ambo Ako; Rinduwati Rinduwati (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Significant population growth has increased demand for beef, while domestic production lags. Poor grazing land management and cattle population pressure remain major constraints, underscoring the need for sustainable solutions. This study aims to develop a system dynamics model and formulate grazing land management strategies to support sustainable beef cattle farming in East Luwu Regency, as one of the cattle production centers in South Sulawesi with extensive but increasingly degraded grazing lands. Conducted from May to July 2025, the model integrated grazing land and cattle population dynamics through causal loop and stock-flow diagrams, while the analytical hierarchy process (AHP) was used to prioritize management strategies. The model reveals that cattle population dynamics are primarily influenced by forage availability, cattle purchases, and birth rates, while grazing land depends on water supply, soil quality, and land availability. From 2020 to 2024, the average grazing land area was 3,013.72 ha with a grass regeneration rate of 1.11 kg ha-1 day-1 and a declining maximum carrying capacity (3,075 ind ha-1 year-1). During the same period, the cattle population averaged 20,411 heads but declined annually by -1,036.5 heads, with a feed ratio of only 0.03% per day, highlighting the urgent need for an effective management strategy. The AHP results indicate that the Integrated Feed Management and Population Control (IFM-PC) strategy achieved the highest score across sustainability criteria, while the reduced stocking rate (SR↓/ha) ranked lowest. This study concludes that grazing land and cattle populations in East Luwu are undergoing considerable degradation, and implementing IFM-PC is crucial for long-term sustainability.